Repetitive Noninvasive Brain Stimulation to Modulate Cognitive Functions in Schizophrenia: A Systematic Review of Primary and Secondary Outcomes - Hasan, Alkomiet (Schizophr Bull, 2016)
Despite many years of research, there is still an urgent need for new therapeutic options for the treatment of cognitive deficits in schizophrenia. Noninvasive brain stimulation (NIBS) has been proposed to be such a novel add-on treatment option. The main objective of this review was to systematically evaluate the cognitive effects of repetitive NIBS in schizophrenia. As most studies have not been specifically designed to investigate cognition as primary outcome, we have focused on both, primary and secondary outcomes. The PubMed/MEDLINE database (1985–2015) was systematically searched for interventional studies investigating the effects of repetitive NIBS on schizophrenia symptoms. All interventional clinical trials using repetitive transcranial stimulation, transcranial theta burst stimulation, and transcranial direct current stimulation for the treatment of schizophrenia were extracted and analyzed with regard to cognitive measures as primary or secondary outcomes. Seventy-six full-text articles were assessed for eligibility of which 33 studies were included in the qualitative synthesis. Of these 33 studies, only 4 studies included cognition as primary outcome, whereas 29 studies included cognitive measures as secondary outcomes. A beneficial effect of frontal NIBS could not be clearly established. No evidence for a cognitive disruptive effect of NIBS (temporal lobe) in schizophrenia could be detected. Finally, a large heterogeneity between studies in terms of inclusion criteria, stimulation parameters, applied cognitive measures, and follow-up intervals was observed. This review provides the first systematic overview regarding cognitive effects of repetitive NIBS in schizophrenia.